University Students’ Reflections on the Challenges, Opportunities, and Lessons Learned during the Global Outbreak - Toquero, Cathy Mae D; al, et (ASEAN Multidisciplinary Research Journal, 2021)
This article is a collective approach that examines the opportunities, challenges, and lessons learned by university students during the COVID-19 pandemic. This multi-authored article invited students at a public institution in the Philippines to submit a response to a call from The Papyrus under the Adviser’s Desk titled, "Educators’ Response to New Educational and Social Realities amid COVID-19." The students reflect on the social and educational challenges they face as they pursue their goals, the educational opportunities they experience while attempting to adjust to the new normal of learning, and the socio-educational lessons they have learned as they envision the next normal. The limitations of this article are inevitable as conventional research process was not applied. However, since COVID-19 is evolving and so is research among students, written reflections of the authors are powerful testimonies that open the gateways to their raw emotions and experiences. Hence, catapulting this article is crucial so that future generations can access this metaphorical piece of circumstantial evidence of what took place amidst a phenomenal event that shaped the dawn of global history.